Evaluation of the pedagogical formation courses in previous and current physical education and sports teacher training programs - Gundogdu, Cemal; Agirbas, Ozturk; Ozen, Yener; Gulacti, Fikret (Sila Science, 2012)
Conducted by Faculties of Education in Turkey, teacher training programs are consisted of three basic fields namely general culture, content knowledge and professional teaching knowledge (teacher training). It's seen that amendments and update have been made on contents of these three fields in certain periods depending upon the needs and developments in science world. This study has been made to assess the teacher training courses belonging to teacher training course of study which was enforced in 1998-1999 academic year and teacher training courses belonging to teacher training courses of study which was enforced in 2006-2007 academic year and the qualifications of these courses in accordance with the viewpoints of the students of the department of physical training and sports teaching. For that purpose 1262 physical training and sports teaching preservice teachers who graduated from previous course of study and 394 of those who graduated from the restructured course of study were conferred. A survey made up of 8 questions was used to determine the views of the preservice teacher. A frequency and percentage (%) calculation was made in SPSS 15.0 for Windows statistics packaged software to the obtained data and further Mann-Whitney U Test was applied in the comparison of the opinions of two groups regarding the articles of the survey due to the fact that obtained data didn't show a normal distribution. As a result of this study it is seen that a high majority of the physical training sports preservice teachers subjected to both pervious and current course of study see the teacher training courses as functional in terms of practicing, those subjected to current course of study see the teacher training courses have a contribution to meaningful learning in terms of goal, content and training status and think more positively on the matter that they get the training in teaching with training courses, that they see the training courses mainly based on memorization, that teacher training courses are taught over the presentation works of the preservice teachers, that they don't find the academic members of the course sufficient in terms of content knowledge and their skills in conveying this knowledge, and that they think more positively on the fact that the contemporary training method and techniques and applied practically in teacher training courses. In addition to this it's also mentioned that the teacher training courses can be taught in internship (candidate) teaching level.
Keywords: Teaching; Physical training and sports teaching; Teacher training; Course of study